PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA ANIMASI UPAYA PENINGKATAN BERPIKIR KRITIS PADA MAPEL PAI KELAS VIII SMPN 3 PURWOKWETO - Ningrum, Nisa Anindia; Kurniawan , Aziz (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2025)
This reseach was conducted based one the low critical PAI thinking skill of class VIII at SMPN 3 Purwokerto. Reseacrhers chose problem based learning models with the helps of animated media to overcome students PAI. The aim of this research was to find out how it was implemenited and whether there was an influence of the problem based learning model with the help of the animated media on students PAI critical thinking abilities. The type of research used was quantitative research using eksperimental quasi methods. The population of this study was all class VIII, totaling 288 students, with sample 35 students in class VIII C, and 35 students in class VIII D. Data collection methods were carried out by observasation and test. Data analysis of the techniques used normality test obtained a value of 0,0637 > 0,05, then H1 accepted. So it cauld be conckuded that there was an influence berween the models problem based learning with the help of animatide media on PAI critical thinking skills.